Organic gladiolus cultivation in first-year no-tillage system - Oliveira, Rivael de Jesus; Lima , Cláudia Simone Madruga; Leandrini, Josimeire Aparecida; Negrelli, Welton Schiles; Oliveira, Luiz Fernando de Jesus; Lizarelli, Heitor Flores (Revista de Ciências Agroveterinárias, 2023)
Cut flowers are considered an important alternative for property diversification, especially in family farming. The culture of gladiolus (Gladiolus x grandiflorus Hort.) is easy to conduct and has good added value. The traditional way of cultivating gladiolus is carried out with intense soil revolution, which can generate losses in the system. Thus, the adoption of sustainable systems becomes important for the balance of agroecosystems, with the No-Till System being one of these options. The objective of this work is to evaluate the agronomic performance of gladiolus in the organic no-tillage system. The experiment was carried out in the Horticulture sector of the Federal University of Fronteira Sul, Laranjeiras do Sul-PR campus. The experiment was carried out in completely randomized blocks with plots containing a mix of ground cover plants composed of black oat (Avena strigosa Schreb) + Vetch (Vicia sativa L.) + forage turnip (Raphanus sativus L.) and cultivation without cover, followed by cultivation of gladiolus. The gladiolus cultivar used was Yester intermediate cycle II. The evaluations carried out were: phenological and morphological characteristics of the crop, physical and biological characteristics of the soil, incidence of phytophagous insects, diseases and weeds, post-harvest viability and productivity. The results of basal soil respiration, soil temperature, weed incidence, total chlorophyll, rod length, largest leaf length, classification of floral stems classification and productivity showed significant differences between the systems. Cultivation with ground cover obtained higher productivity, with an average of 79,666 stems per hectare. The no-tillage system with organic management showed satisfactory agronomic results, being indicated for the cultivation of gladioli.